MAKNA KEBAHAGIAAN LANSIA YANG TINGGAL SENDIRIAN DI RUMAH - Nurul Hidayah; Septia Purwandani, Rizky Aulia Fitriana, Indira Mustika Tandiono (CV. ADIBA AISHA AMIRA, 2025)
In today’s era, many eldery people live alone at home, they don’t want to live in nursing home or live with their children because they feel more comfortable living in their own home. The findings of this research show that many eldery people find happiness even though they live alone at home. This research discusses eldery people who live alone at home in interpreting the meaning of happiness in their remaining years. This research uses a type qualitative research with a phenomenological approach which is carried out to understand a phenomenon with relatively similiar characteristics. Respondent involved in this research used a purposive sampling technique. Data collection methods used interview and observation of 3 eldery people in RT 01,RW 10, Sanan Wetan Blitar jawa Timur. The results of this research show that even though the subject are eldery and live at home alone, they feel happy because they are healthy and some are still able to earn a living, have peers, and active in social life.